PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWANDI BPJS KESEHATAN KANTOR CABANG LANGSA - Saviqa Intan Maulida Bakri (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The purpose of this study was to obtain empirical evidence of: (1) Style leadership Motivation influential work in “BPJS Kesehatan”Langsa Branch office ; (2) Provision of job satisfaction influence the motivation to work in “BPJS Kesehatan” Langsa Branch office; (3) Style leadership Attainment of an effect on employees performance at “BPJS Kesehatan”Langsa Branch office; (4) Provision of Jab Satisfactioneffect the employees performance at “BPJS Kesehatan”Langsa Branch office; (5) Motivation of Achievement affect the employees performance at “BPJS Kesehatan”Langsa Branch Office. In connection with the research objectives, the population of this study is an employee / employees of “BPJS Kesehatan”Langsa Branch office. Total population employee / employees who actively work in “BPJS Kesehatan”Langsa Branch Officeis 47 people. Data analysis method withpath analysis. The results showed that: (1) Style leadership positive and significant impact on work motivation in “BPJS Kesehatan” Langsa Branch officeof 0.384 or 38,4%; (2) Provision of Jab Satisfactionpositive and significant impact on work motivation in “BPJS Kesehatan” Langsa Branch officeof 0.584 or 58.4%; (3) Style leadership positive and significant impact on the employees performancein “BPJS Kesehatan” Langsa Branch office of 0.235 or 23.5%; (4) Provision of Jab Satisfaction positive and significant impact on the employees performancein “BPJS Kesehatan” Langsa Branch officeof 0.151 or 15.1%; (5) work motivation is positive and significant effect on the achievement of employees performancein “BPJS Kesehatan” Langsa Branch office of 0.569 or 56.9%.